Reduplication in Tagalog and Indonesian Language (Bahasa): A Comparative Study - Hilma Safitri; Nikomang Ariani; Diah Intan Pratiwi (Universitas Cokroaminoto Palopo, 2024)
Reduplication consists of many forms in which each form has a tendency to create error effecting the meanings. The absence of knowledge to construct words appropriately creates difficulties since not all words are readily constructed for word reduplication. Less studies on topic applied were conducted. Therefore, this study is worth doing. The paper aims to describe and to compare the morphological reduplication in both Tagalog and Indonesian Language (Bahasa). This research was a qualitative methods. Qualitative research is a methods used to conduct and to interpret data in accordance with strategies such as collecting, analyzing, and concluding (Hamied, 2017). The data were analyzed by listing and comparing form and meaning of words after they were reduplicated. The findings show that the reduplication in both languages similarities and differences lie in terms of changes of tenses, class, another meaning, and quantity. Both partial and full reduplications were also found in terms of their similarities and differences. Partial reduplication on the words in the morphological reduplication altered two components namely word formation and the word meaning which lied in the changes of tenses which was the most common reduplication in Tagalog language. Meanwhile in Bahasa was the reduplication which referred to quantity. Full reduplication changing took place in the term of words with affix [ka] indicates the changes of meaning and the form as well. In the case of reduplication taken place on Bahasa, it was found that Bahasa had the tendency to have different meanings.